Tantangan Guru dalam Meningkatkan Nilai Moral Siswa Generasi Z: Studi kasus Bullying di Sekolah Dasar - sihite, Dorawan Lia; Sari, Tri Indah; Beru PA, Reh Bungana; Setiawan, Deny (Piramida Akademi, 2023)
21st century humans as thinking creatures elaborate the phenomenon of technological progress as a whole by balancing the elements within it. The abilities that need to be possessed to balance knowledge with 21st century skills are life and career skills, learning and innovation skills, technology and information media skills. Generation Z is a lifestyle technology generation whose globalization has become a trend for Generation Z which has a positive impact on the progress of civilization, knowledge and so on. However, it cannot be denied that there are negative impacts in using technology, one of which is moral development. The problems caused by the use of social media are that most generation Z are less skilled at communicating in the real world. The aim of instilling moral values is to instill moral values that are starting to fade in children's environment due to the bad influences they receive so that it is hoped that children in the future will have good morals, because if left untreated from childhood it will possibly destroy the next generation. -young generations in the future. This research uses a research library (Library Study). The aim of this research is to find out what the challenges are for a teacher in improving moral values in generation Z students. A teacher must be able to change teaching styles and discover the latest concepts so that students can understand and prepare well for the future. Instilling morals in elementary schools in the right way in the teaching and learning process can be one of the main goals in the field of education in producing a quality generation in order to build moral human resources. Especially in this era of society 5.0, critical thinking, creativity, collaboration and communication skills are very important for students because they provide preparation for generation Z in developing themselves in the future, including in cases of bullying.